Literature Review: Contextual Teaching and Learning on Islamic ReligiousEducation Materials - Chairul Anwar (Education Studies and Teaching Journal (EDUTECH), 2024)
This research aims to describe the concept of contextual teaching and learning (CTL) inthe teaching and learning process. The research method used is library research. Thedata obtained is then analyzed and studied in depth regarding the references used, as isthe case in library research. This research explains that contextual teaching and learning(CTL) has a normative basis which becomes a basis or reference for use in teachingIslamic religious education material in schools or madrasas.. The results of the analysisare that conceptually CTL is a type of approach that uses an integrated perspectiveand/or analytical method. Learning processes that are possible to be integrated need tobe discussed to find similarities and uses, so that they can be more comprehensive andmore contextual. The application of this paradigm has been described as having severalobstacles when evaluated. The application of contextual teaching and learning in theclassroom gives students the opportunity to develop themselves for independent andcollaborative learning. The application of CTL is also very synergistic with PAI material,so that the development of teaching materials can be accepted by students. Thefindings of this research can be a reference for further similar research on the conceptof integrative interconnection in the future.